Deficiency in pulmonary surfactant proteins in mice with fatty acid binding protein 4‐Cre‐mediated knockout of the tuberous sclerosis complex 1 gene. Issue 3 (7th December 2012) - Xiang, Xinxin; Yuan, Fang; Zhao, Jing; Li, Ziru; Wang, Xian; Guan, Youfei; Tang, Chaoshu; Sun, Guang; Li, Yin; Zhang, Weizhen
<x xml:space="preserve">Abstract</x> Tuberous sclerosis complex 1 (TSC1) forms a heterodimmer with tuberous sclerosis complex 2, to inhibit signalling by the mammalian target of rapamycin (mTOR) complex 1 (mTORC1). The mTORC1 stimulates cell growth by promoting anabolic cellular processes, such as gene transcription and protein translation, in response to growth factors and nutrient signals. Originally designed to test the role of TSC1 in adipocyte function, mice in which the gene for TSC1 was specifically deleted by the fatty acid binding protein 4 (FABP4)‐Cre (Fabp4‐Tsc1cKO mice) died prematurely within 48 h after birth. The Fabp4‐Tsc1cKO mouse revealed a much smaller phenotype relative to the wild‐type littermates. Maternal administration of rapamycin, a classical mTOR inhibitor, significantly increased the survival time of Fabp4‐Tsc1cKO mice for up to 23 days. Both macroscopic and microscopic haemorrhages were observed in the lungs of Fabp4‐Tsc1cKO mice, while other tissues showed no significant changes. Levels of surfactant proteins A and B demonstrated a significant decrease in the Fabp4‐Tsc1cKO mice, which was rescued by maternal injection of rapamycin. Co‐localization of FABP4 or TSC1 with surfactant protein B was also detected in neonatal pulmonary tissues. Our study suggests that TSC1–mTORC1 may be critical for the synthesis of surfactant proteins A and B.